Subiekt semantyczny w zdaniach typu „Ему хочется спать” w porównaniu z językiem polskim - Rudyk, Anna (Studia Rossica Posnaniensia, 2015)
This article deals with the ways in which the semantic subject is expressed in Russian sentences such as “Ему хочется спать” and in their Polish equivalents. The dative case is the only explicit way to indicate the semantic subject. This kind of subject can also be ascertained from the context or remain undetermined if information about its referent is missing.